2004
DOI: 10.1093/ajcn/79.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Dealcoholized red wine decreases atherosclerosis in apolipoprotein E gene–deficient mice independently of inhibition of lipid peroxidation in the artery wall

Abstract: DRW contains polyphenolic compounds capable of synergizing with vitamin E, and long-term moderate consumption of DRW can decrease atherosclerosis in apolipoprotein E gene-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 52 publications
8
40
0
Order By: Relevance
“…In addition, there is evidence that in human lesions oxidized lipids associated with LDL accumulate substantially only late in disease development, after accumulation of unoxidized cholesterol and cholesterol esters (966). Furthermore, lipoprotein lipid oxidation can be dissociated from disease in animal models of atherosclerosis (899,1005,1054,1055). While these studies do not support a cornerstone of the oxidative modification hypothesis of atherosclerosis, namely, that LDL oxidation in the artery wall is an early event in the genesis of the disease and that it contributes to subsequent lipid accumulation, the data do not directly address the causal or temporal relationship between intracellular oxidative stress and disease progression.…”
Section: Ldl Oxidation Versus Atherosclerosismentioning
confidence: 91%
“…In addition, there is evidence that in human lesions oxidized lipids associated with LDL accumulate substantially only late in disease development, after accumulation of unoxidized cholesterol and cholesterol esters (966). Furthermore, lipoprotein lipid oxidation can be dissociated from disease in animal models of atherosclerosis (899,1005,1054,1055). While these studies do not support a cornerstone of the oxidative modification hypothesis of atherosclerosis, namely, that LDL oxidation in the artery wall is an early event in the genesis of the disease and that it contributes to subsequent lipid accumulation, the data do not directly address the causal or temporal relationship between intracellular oxidative stress and disease progression.…”
Section: Ldl Oxidation Versus Atherosclerosismentioning
confidence: 91%
“…In particular, quercetin and theaflavin significantly attenuated lesion formation in ApoE Ϫ/Ϫ mice. Previous studies have shown that polyphenol-rich beverages, such as red wine, 21 dealcoholized red wine, 22 and tea, 27 can inhibit atherosclerosis in ApoE Ϫ/Ϫ mice. These beverages contain a complex mixture of polyphenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…22 The aorta was rinsed in phosphate-buffered saline (PBS) after removal from the phosphate-buffered formaldehyde (4% by volume; pH, 7.0 to 7.3) and processed as described in the Supplemental Material. For immunohistochemistry of heme oxygenase-1 (HO-1), paraffin-embedded thoracic aorta specimens were sectioned every 400 m, proximally from the third pair of intercostal arteries, for a total distance of 2800 m. HO-1 protein was detected with anti-rat HO-1 polyclonal rabbit antibody (SPA-895; Stressgen, Ann Arbor, Mich) (final concentration, 10 g/mL), applied for 24 hours at 4°C.…”
Section: Histological Analysis Of Mouse Aorta Specimensmentioning
confidence: 99%
“…They have been recognized as health-promoting functional food ingredients due to their antioxidant activity (Nam et al 2006;Philpott et al 2006;Satue-Gracia et al 1997), which has been reported to reduce the risk of coronary heart disease (Stocker and O'Halloran 2004;Waterhouse 1995). Anthocyanins are also known to have anti-cancer (Hyun and Chung 2004;Kamei et al 1995;Zhao et al 2004), hypoglycemic (Tsuda et al 2003), and anti-inflammatory effects (Tsuda et al 2002) and have been used in the treatment of various circulatory disorders (Bettini et al 1985).…”
Section: Introductionmentioning
confidence: 99%